2021
DOI: 10.1126/sciadv.abf3641
|View full text |Cite
|
Sign up to set email alerts
|

Single-molecule measurements reveal that PARP1 condenses DNA by loop stabilization

Abstract: Poly(ADP-ribose) polymerase 1 (PARP1) is an abundant nuclear enzyme that plays important roles in DNA repair, chromatin organization and transcription regulation. Although binding and activation of PARP1 by DNA damage sites has been extensively studied, little is known about how PARP1 binds to long stretches of undamaged DNA and how it could shape chromatin architecture. Here, using single-molecule techniques, we show that PARP1 binds and condenses undamaged, kilobase-length DNA subject to sub-piconewton mecha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 71 publications
1
18
1
Order By: Relevance
“…Prior to this study, the forces generated by co-condensation between DNA and proteins-such as FoxA1 and PARP1-were estimated to be on the order of sub-pN, placing them among the weakest nuclear forces alongside those generated by loop-extruding SMC complexes such as condensin and cohesin. 9,13,21 Here we show that Sox2, an abundant TF central to pluripotency and embryogenesis, can actively generate condensation forces up to 7 pN, one order of magnitude higher than previously reported values. It is worth noting that Klf4, another pluripotency TF, can also form condensates on DNA against a relatively high force (~8 pN) according to a recent report.…”
Section: Discussioncontrasting
confidence: 50%
See 3 more Smart Citations
“…Prior to this study, the forces generated by co-condensation between DNA and proteins-such as FoxA1 and PARP1-were estimated to be on the order of sub-pN, placing them among the weakest nuclear forces alongside those generated by loop-extruding SMC complexes such as condensin and cohesin. 9,13,21 Here we show that Sox2, an abundant TF central to pluripotency and embryogenesis, can actively generate condensation forces up to 7 pN, one order of magnitude higher than previously reported values. It is worth noting that Klf4, another pluripotency TF, can also form condensates on DNA against a relatively high force (~8 pN) according to a recent report.…”
Section: Discussioncontrasting
confidence: 50%
“…[2][3][4][5] These nuclear compartments, or transcriptional hubs, connect enhancers to promoters, recruit the RNA polymerase and its regulators, and control gene expression in a dynamic fashion. 6,7 Notably, some TFs have been shown to form co-condensates with DNA, [8][9][10][11] which ensnare an amount of DNA into the condensates and thus exert tension on the outside free DNA. 12 The force generated by such protein-DNA co-condensation was reported to be in the sub-piconewton (pN) range.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The PARP protein family mediates the PARylation of the translated substrate proteins involved in transcription and DNA damage repair, and PARP1 is a particularly important protein for detecting single-stranded DNA breaks (SSBs) [40]. A recent study showed that PARP1 can condenses DNA via loop stabilization [41]. The increased expression of PARP1 is also an important factor that mediates the drug resistance of tumor chemotherapy, especially the drug resistance related to DNA loss [42].…”
Section: Discussionmentioning
confidence: 99%